Effects of Calcium and Signal Sensing Systems on Azorhizobium caulinodans Biofilm Formation and Host Colonization - Liu, Xiaolin; Zhang, Kaiye; Liu, Yanan; Zou, Desheng; Wang, Dandan; Xie, Zhihong (Frontiers in Microbiology, 2020)
Biofilm formation is important for establishing plants-microbe associations. The role of calcium on biofilm formation has been studied in many bacteria except rhizobia. In this study, we investigated the role of calcium for biofilm formation in Azorhizobium caulindans, which forms nodules in the stem and root of its host plant Sesbania rostrata. We found that calcium is essential for A. caulindans biofilm formation, in addition to the presence of extracellular matrix components, eDNA and proteins. Also, calcium-mediated biofilm formation was tested with chemotaxis, motility, cyclic di-GMP synthesis, and quorum sensing mutants. Finally, calcium was found to promote S. rostrata root colonization of A. caulinodans. In total, these results show that calcium is essential for A. caulindans biofilm formation, and it affects the interaction between A. caulinodans and host plant.